Cerebrospinal fluid β2-microglobulin promotes the tau pathology through microglia–astrocyte communication in Alzheimer's disease - Zehu Sheng; Lanyang Wang; Ming Chen; Fuxin Zhong; Shijing Wu; Shuyu Liang; Jiaqi Song; Lihua Chen; Yingxi Chen; Shiyu Chen; Weihua Yu; Yang Lü (Alzheimer’s Research & Therapy)
Abstract Background Cerebrospinal fluid (CSF) β2-microglobulin (β2M) has been demonstrated as an important factor in β-amyloid (Aβ) neurotoxicity and a potential target for Alzheimer’s disease (AD). However, more investigation is required to ascertain the relationship between β2M and glial activities in AD pathogenesis. Methods In this study, 211 participants from the Alzheimer’s disease Neuroimaging Initiative (ADNI) with CSF and Plasma β2M, CSF glial fibrillary acidic protein (GFAP), soluble triggering receptor expressed on myeloid cells 2 (sTREM2), Aβ42, phosphorylated-tau (P-tau) and total tau (T-tau) were divided into four groups, stage 0, 1, 2, and suspected non-AD pathology (SNAP) based on the National Institute on Aging- Alzheimer’s Association (NIA-AA) criteria. Multiple linear regression, linear mixed effects models, and causal mediation analyses bootstrapped 10,000 iterations were used to investigate the underlying associations among β2M and CSF biomarkers at baseline and during a longitudinal visit. Results CSF β2M concentration decreased with amyloid in stage 1 compared with stage 0 and increased with tau pathology and neurodegeneration in stage 2 and SNAP compared with stage 1. Moreover, CSF β2M level was positively correlated with the Aβ42 (β = 0.230), P-tau (β = 0.564), T-tau (β = 0.603), GFAP (β = 0.552), and sTREM2 (β = 0.641) (all P < 0.001). CSF β2M was only longitudinally correlated with T-tau change. The correlation of CSF β2M with P-tau (proportion = 25.4%, P < 0.001) and T-tau (proportion = 26.7%, P < 0.001) was partially mediated by GFAP in total participants, reproduced in late-life individuals. Furthermore, the astrocyte cascade also partially mediated the pathological relationship between CSF β2M and tau pathology (β2M → GFAP → YKL-40 → P-tau/T-tau, IE: 0.424—0.435, all P < 0.001). Nevertheless, the mediation effects of sTREM2 were not significant. Additionally, there was no association between plasma β2M and CSF biomarkers. Conclusions CSF β2M is dynamic in AD pathology and associated with neuroinflammation. CSF GFAP might mediate the association between β2M and tau pathology, complementing the existing research on the effect of β2M in AD pathology and providing a new perspective on treatment.